If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4b + -5) = 23 Reorder the terms: 6(-5 + 4b) = 23 (-5 * 6 + 4b * 6) = 23 (-30 + 24b) = 23 Solving -30 + 24b = 23 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 24b = 23 + 30 Combine like terms: -30 + 30 = 0 0 + 24b = 23 + 30 24b = 23 + 30 Combine like terms: 23 + 30 = 53 24b = 53 Divide each side by '24'. b = 2.208333333 Simplifying b = 2.208333333
| (4w+3)(8+w)=0 | | 2(4t-2)+t=16t | | ((2/x)+3)=((5x-7)/x) | | 6(y-1)+5y-6=65 | | X^2+9x+6/(x+6) | | x^2+(7/2)x-2 | | 8c-3=5 | | 4+2h=10 | | 14-2(3p+1)=2(3a-2) | | 5p+3p-7=6p+21 | | (4+2)3= | | (8x-45)=(10-x/3) | | 4x^2-5x+8= | | 3(y+4)=5y+y | | 7=3+2y | | 16x^2-112x+160=0 | | 3/2x+5/2x | | 40x+120=720 | | n^2-9n+18=0 | | 1/x+2+1/x=1 | | 4x+3(2x-6y)=y | | 3g+4=10 | | 5y=3y+36 | | X^2+8x+6=13x | | 2p+2=10 | | 8a+7=7a+8a | | -7-5r=12(-9r+5) | | (7x)/(x-3)-(21)/(x-3) | | 18+18+25+2/3x | | 23x-3=3x+7 | | 7(-5x-11)=-357 | | 614/14-53/14 |